Halloween party murder - Meier, Leslie; Hollis, Lee; Ross, Barbara, 1953- (Kensington Publishing Corp., 2021)
Three novellas from three cozy mystery writers all feature murders that happen at Halloween parties, including a fête in a Victorian home where someone overdoses on tainted drugs and a teenage sleepover where the attendees discover a murdered neighbor.